Loss of CFTR function is associated with reduced bitter taste receptor-stimulated nitric oxide innate immune responses in nasal epithelial cells and macrophages - Carey, Ryan M.; Palmer, James N.; Adappa, Nithin D.; Lee, Robert J. (Frontiers in Immunology, 2023)
Bitter taste receptors (T2Rs) are G protein-coupled receptors identified on the tongue but expressed all over the body, including in airway cilia and macrophages, where T2Rs serve an immune role. T2R isoforms detect bitter metabolites (quinolones and acyl-homoserine lactones) secreted by gram negative bacteria, including Pseudomonas aeruginosa, a major pathogen in cystic fibrosis (CF). T2R activation by bitter bacterial products triggers calcium-dependent nitric oxide (NO) production. In airway cells, the NO increases mucociliary clearance and has direct antibacterial properties. In macrophages, the same pathway enhances phagocytosis. Because prior studies linked CF with reduced NO, we hypothesized that CF cells may have reduced T2R/NO responses. Using qPCR, immunofluorescence, and live cell imaging of air-liquid interface cultures, we found primary nasal epithelial cells from both CF and non-CF patients exhibited similar T2R expression, localization, and calcium signals. However, CF cells exhibited reduced NO production also observed in immortalized CFBE41o- CF cells and non-CF 16HBE cells CRISPR modified with CF-causing mutations in the CF transmembrane conductance regulator (CFTR). NO was restored by VX-770/VX-809 corrector/potentiator pre-treatment, suggesting reduced NO in CF cells is due to loss of CFTR function. In nasal cells, reduced NO correlated with reduced ciliary and antibacterial responses. In primary human macrophages, inhibition of CFTR reduced NO production and phagocytosis during T2R stimulation. Together, these data suggest an intrinsic deficiency in T2R/NO signaling caused by loss of CFTR function that may contribute to intrinsic susceptibilities of CF patients to P. aeruginosa and other gram-negative bacteria that activate T2Rs.